Konsep Ekosufisme dalam Perspektif Sayyed Hossein Nasr - Anggriani, Nendy Maulaya; Nasution, Hasyimsyah; Harahap, Hotmatua Paralihan (Lembaga Yasin AlSys, 2023)
Sayyed Hossein Nasr's deep reflections on God, nature and humans, his teachings on the environmental crisis facing modern humans today due to the lack of harmony between God, nature and humans should have a very bad impact on ecosystems. Given this, it is important to increase research on ecology because the lack of spiritual values in modern The environment will be impacted by society. This study uses library research methods with a qualitative approach. With an Islamic philosophy approach and studying primary and secondary sources in the form of books, journals and other related articles. Nasr's thoughts on ecological Sufism made a significant contribution to the ecological movement in the Islamic world. He helps articulate the Muslim vision of the environment and links it to Islamic spiritual concepts. This has encouraged many Muslims to care more about the environment and seek faith-based solutions.